US and Cross-National Policies, Practices, and Preparation
XII, 196 p.
Keywords: As educational policy trends converge in many countries, such as demands for greater accountability, decentralization, and more culturally sensitive practices for an increasingly diverse student body, there is growing interest in cross-national comparisons and generalizations about leadership qualities and practices that result in successful schools. US and Cross-National Policies, Practices and Preparation: Implications for Successful Instructional Leadership, Organizational Learning, and Culturally Responsive Practices fills that need by bringing together triads of scholars from the International Study of Successful School Principals (ISSPP) to make direct comparisons among policies and practices in the U.S. with those in other national contexts, and then to draw implications for improving leadership preparation. This book provides theories and empirical case study examples of instructional leadership, organizational learning, and culturally responsive practices as they are shaped by political, economic, and cultural factors in seven different national contexts. The seven countries featured in this book are the U.S., Australia, Denmark, England, Sweden, Norway, and Cyprus. The book begins with an overview of the ISSPP, including its underlying theoretical framework, its research methodologies employed, its limitations and how analyses of the project’s data and findings evolved from the first phase of the study to its current focus.